Bioinformatics proficiency among African students - Akintola, Ashraf Akintayo; Aborode, Abdullahi Tunde; Hamza, Muhammed Taofiq; Amakiri, Augustine; Moore, Benjamin; Abdulai, Suliat; Iyiola, Oluyinka Ajibola; Sulaimon, Lateef Adegboyega; Effiong, Effiong; Ogunyemi, Adedeji; Dosunmu, Boluwatife; Maigoro, Abdulkadir Yusif; et al. (Frontiers in Bioinformatics, 2024)
Bioinformatics, the interdisciplinary field that combines biology, computer science, and data analysis, plays a pivotal role in advancing our understanding of life sciences. In the African context, where the diversity of biological resources and healthcare challenges is substantial, fostering bioinformatics literacy and proficiency among students is important. This perspective provides an overview of the state of bioinformatics literacy among African students, highlighting the significance, challenges, and potential solutions in addressing this critical educational gap. It proposes various strategies to enhance bioinformatics literacy among African students. These include expanding educational resources, fostering collaboration between institutions, and engaging students in research projects. By addressing the current challenges and implementing comprehensive strategies, African students can harness the power of bioinformatics to contribute to innovative solutions in healthcare, agriculture, and biodiversity conservation, ultimately advancing the continent's scientific capabilities and improving the quality of life for her people. In conclusion, promoting bioinformatics literacy among African students is imperative for the continent's scientific development and advancing frontiers of biological research.